2016
DOI: 10.1515/bjdm-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Caries prevalence among 24 to 71-month old children from Banja Luka

Abstract: Summary Background: Despite the availability of a variety of preventive and treatment modalities, caries in the early childhood remains a serious and prevalent disease worldwide.The aim of this study was to assess the prevalence of early childhood caries (ECC) among 24 to 71-month old children who attended the Center for preschool education Banja Luka, Republic of Srpska, Bosnia and Herzegovina.Material and Methods: This was a cross-sectional study. The whole sample included 297 children of both genders. Carie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…Oral health has been an important aspect of an adult, as well as, children well-being and quality of life. Untreated dental caries associated with discomfort/pain can affect weight gain, normal growth and child's development, therefore preventive and therapeutic measures must be based on the most current scientific and clinical knowledge available [3]. Although the Health Insurance Fund of Bosnia and Herzegovina covers full costs of dental care for children younger than 15-years, the ECC prevalence is extremely high and most of the lesions are untreated [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral health has been an important aspect of an adult, as well as, children well-being and quality of life. Untreated dental caries associated with discomfort/pain can affect weight gain, normal growth and child's development, therefore preventive and therapeutic measures must be based on the most current scientific and clinical knowledge available [3]. Although the Health Insurance Fund of Bosnia and Herzegovina covers full costs of dental care for children younger than 15-years, the ECC prevalence is extremely high and most of the lesions are untreated [3].…”
Section: Discussionmentioning
confidence: 99%
“…Untreated dental caries associated with discomfort/pain can affect weight gain, normal growth and child's development, therefore preventive and therapeutic measures must be based on the most current scientific and clinical knowledge available [3]. Although the Health Insurance Fund of Bosnia and Herzegovina covers full costs of dental care for children younger than 15-years, the ECC prevalence is extremely high and most of the lesions are untreated [3]. In countries like Bosnia and Herzegovina, with high caries prevalence, caries risk assessment is very important, but there is only data about caries risk assessment in the 12-years-old children [19] and pregnant women [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it remains a huge problem both in developed and in developing countries. 2,3 Data on the prevalence of Severe Early Childhood Caries (S-ECC) in Banja Luka municipality was 34.9%. 3 Many studies have demonstrated the association of MS (mutans streptococci) with ECC.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Data on the prevalence of Severe Early Childhood Caries (S-ECC) in Banja Luka municipality was 34.9%. 3 Many studies have demonstrated the association of MS (mutans streptococci) with ECC. [4][5][6][7] The systematic reviews confirmed that maternal factors influence bacterial acquisition, whereas colonization was mostly mediated by oral health and feeding habits 8,9 during the first year of life.…”
Section: Introductionmentioning
confidence: 99%